The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1002/jat.1793
|View full text |Cite
|
Sign up to set email alerts
|

Aluminium chloride promotes anchorage‐independent growth in human mammary epithelial cells

Abstract: Aluminium salts used as antiperspirants have been incriminated as contributing to breast cancer incidence in Western societies. To date, very little or no epidemiological or experimental data confirm or infirm this hypothesis. We report here that in MCF-10A human mammary epithelial cells, a well-established normal human mammary epithelial cell model, long-term exposure to aluminium chloride (AlCl 3 ) concentrations of 10-300 mM, i.e. up to 100 000-fold lower than those found in antiperspirants, and in the rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
76
2
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(89 citation statements)
references
References 32 publications
8
76
2
1
Order By: Relevance
“…Sappino et al (2012) investigated 0, 10, 100 or 300 μM AlCl 3 or ACH (purity ≥ 99%) in cultured MCF-10A cells and in cultured human primary mammary epithelial cells. Sappino et al (2012) suggested that “at the expected pH of the cell culture medium (pH ~7.2), AlCl 3 and ACH yield the same dissociation product, aluminum hydroxide”.…”
Section: Immunology and Vaccine Adjuvantsmentioning
confidence: 99%
“…Sappino et al (2012) investigated 0, 10, 100 or 300 μM AlCl 3 or ACH (purity ≥ 99%) in cultured MCF-10A cells and in cultured human primary mammary epithelial cells. Sappino et al (2012) suggested that “at the expected pH of the cell culture medium (pH ~7.2), AlCl 3 and ACH yield the same dissociation product, aluminum hydroxide”.…”
Section: Immunology and Vaccine Adjuvantsmentioning
confidence: 99%
“…Silva et al (2012) found that the following metals were capable of binding to cellular estrogen receptors and then mimicking the actions of physiological estrogens: "aluminium, antimony, arsenite, barium, cadmium, chromium (Cr(II)), cobalt, copper, lead, mercury, nickel, selenite, tin and vanadate" [296,297]. Al has recently been identified in breast cancer tissue [298,299], with a significantly higher concentration in the upper outer quadrant of the breast than in the inner (middle and medial) regions. In 2012, Sappino et al [299] found that, in MCF-10A human mammary epithelial cells, a well-established normal human mammary epithelial cell model, long-term exposure to aluminum chloride (AlCl 3 ) concentrations of 10-300 μM, i.e.…”
Section: Breast Cancermentioning
confidence: 99%
“…Al has recently been identified in breast cancer tissue [298,299], with a significantly higher concentration in the upper outer quadrant of the breast than in the inner (middle and medial) regions. In 2012, Sappino et al [299] found that, in MCF-10A human mammary epithelial cells, a well-established normal human mammary epithelial cell model, long-term exposure to aluminum chloride (AlCl 3 ) concentrations of 10-300 μM, i.e. up to 100,000-fold lower than those found in antiperspirants, and in the range of those recently measured in the human breast, results in loss of contact inhibition and anchorage-independent growth.…”
Section: Breast Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, findings of this study documented fact that the adenocarcinoma of human prostate accumulates high levels of many trace elements including Al, B, Be, Bi, Cr, Fe, Hg, Ni, Sn, Th, and Zr. Genotoxicity and carcinogenicity of these elements are well known (Anghileri et al, 2000;Gordon & Bowser, 2003;Crespo-López et al, 2009;Bian et al, 2011;Gonzalez-Vasconcellos et al, 2011;Müezzinoğlu et al, 2011;Sappino et al, 2012;Helmig et al, 2013;Adámik et al, 2015;Farasani & Darbre, 2015). On the other hand, compared to human body soft tissues, the normal prostate of young adults has higher levels of many trace elements, including Zn (V. Zaichick & S. Zaichick, 2013, 2013a, 2013b, 2013c, 2014d.…”
Section: Resultsmentioning
confidence: 99%